2013
DOI: 10.2190/om.66.2.e
|View full text |Cite
|
Sign up to set email alerts
|

Quality Insights of University Teachers on Dying, Death, and Death Education

Abstract: One of the main responsibilities of teachers is to help individual students cope with life difficulties such as grief following a death. However, very little research explores teachers' views on death, dying, and how they handle grief and loss in schools. This study aims to explore university teachers' knowledge and attitudes on dying, death, and death education. Fifteen university teachers were recruited using a qualitative method. This study reveals that most teachers' views on death and related issues are l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 31 publications
0
12
0
1
Order By: Relevance
“…Some of the participants stated that they felt uncomfortable and helpless when intervening in processes of grief and loss with the students. Literature shows that, even though there are authors who point out that teachers are willing to offer their help (Potts, 2013), there is generally a deep sense of discomfort when dealing with death and grief (Alisic, 2011;Mak, 2012), as well as rejection, bargaining, depression, shock, disbelief, sadness, and feelings of guilt (Mak, 2012). The teachers who have to deal with death and grief report a lack of training on this subject (Lane et al, 2014;Potts, 2013), in spite of it being a common experience.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the participants stated that they felt uncomfortable and helpless when intervening in processes of grief and loss with the students. Literature shows that, even though there are authors who point out that teachers are willing to offer their help (Potts, 2013), there is generally a deep sense of discomfort when dealing with death and grief (Alisic, 2011;Mak, 2012), as well as rejection, bargaining, depression, shock, disbelief, sadness, and feelings of guilt (Mak, 2012). The teachers who have to deal with death and grief report a lack of training on this subject (Lane et al, 2014;Potts, 2013), in spite of it being a common experience.…”
Section: Discussionmentioning
confidence: 99%
“…One aspect of preparation that teachers mentioned was that education could not help them with was that each death would be different for them personally, and even course work or best practices could not help them know how they were going to react in each situation. Mak (2013), however, found that only people who had significant background education with death and dying were ready to address death in the classroom. Since none of the participants in this study have a strong history of death education and the majority claimed they were not comfortable discussing death, it is logical to assume that death education at least partially prepares teachers to discuss death in the classroom.…”
Section: Rq3: How Do Teachers Describe Their Experiences With Death Ementioning
confidence: 99%
“…Like death, dying also has a negative connotation. To some, the dying process is long, painful, marked by disease, sickly physical appearance, and the deterioration of the mind and body (Mak, 2013). Wittenberg-Lyles (2006), however, interviewed hospice care volunteers who had worked with dying patients to gain insight from their experiences.…”
Section: Review Of Literaturementioning
confidence: 99%
See 2 more Smart Citations